GaAs absorber grown at low temperature used in passively Q-switched diode pumped solid state laser - Wang, Yonggang; Ma, Xiaoyu; Wang, CuiLuan; Lin, Tao; Zhen, Kai; Wang, Jun; Zhong, Li; Jia, YuLei; Wei, ZhiYi (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
We report, for the first time to the best of our knowledge, on a passively Q-switched Nd:YVO4 laser with a GaAs absorber grown at low temperature (LT) by metal organic vapor phase expitaxy. Using the LT GaAs absorber as well as an output coupler, a passively Q-switched laser whose pulse duration is as short as 90 ns was obtained.
Optica Applicata, Vol. 36, 2006, nr 1, s. 23-28
Keywords: optyka; GaAs; low temperature; Q-switch; Nd:YVO4 laser